Il paesaggio della Grecia nei Taccuini - Santoli, Carlo (Archivio d’Annunzio, 2016)
D’Annunzio does not dream, but really sees, leading an impressionistic and syncopated storytelling in which he portrays scenes of true reality. Léon Bakst (author of the theatrical productions of the Martyre de Saint Sébastien, La Pisanelle and Phaedra) similarly proceeds, drawing in some works, Narcisse (1911), L'Après-midi d'un Faune (1912), Daphnis et Chloé (1912), Helene de Sparte (1912), those figurative motifs that the poet notes in his travels, such as the intense green of nature, the austere red rocks, the arid and wild lands.